Data intellectual property is the extending of intellectual property rights from reality to cyberspace - YE Yazhen; ZHU Yangyong (大数据)
Data intellectual property has garnered significant attention as a crucial component of the data property rights system. Despite the rapid development of data intellectual property practices, there remains academic debate regarding whether it is necessary to establish data intellectual property rights and how such rights should be structured. In this context, the existence of intellectual property in the form of data is analyzed, and three types of datasets that could be endowed with intellectual property rights are identified. The necessity of creating novel data intellectual property rights is discussed from the perspectives of newly protected subject matter, innovative identification methods, and enhanced protection mechanisms. A definition of data intellectual property is proposed, and a conceptual framework is constructed in which intellectual property extends from the reality to cyberspace, thereby providing theoretical support for the advancement of data intellectual property.